Minds made for stories : how we really read and write informational and persuasive texts - Newkirk, Thomas, ....- (Portsmouth : Heinemann, 2014)
Narrative is regularly considered a type of writing - often an "easy" one, appropriate for early grades but giving away to argument and analysis in later grades. This groundbreaking book challenges all that. It invites readers to imagine narrative as something more - as the primary way we understand our world and ourselves. "To deny the centrality of narrative is to deny our own nature," Newkirk explains. "We seek companionship of a narrator who maintains our attention, and perhaps affection. We are not made for objectivity and pure abstraction - for timelessness. We have 'literary minds' that respond to plot, character, and details in all kinds of writing. As humans, we must tell stories." When we are engaged readers, we follow a story constructed by the author, regardless of the type of writing. To sustain a reading - in a novel, an opinion essay, or a research article - we need a "plot" that helps us comprehend specific information, or we need te experience the significance of an argument. As Robert Frost reminds us, all good memorable writing is "dramatic". Minds made for stories is a needed corrective to the narrow and compartmentalized approaches often imposed on schools - approaches which are at odds with the way writing really works outside school walls.
Keywords: Schrijven